Impact of Central Quarantine Inside a Lockdown Hospital Due to COVID-19 Pandemic on Psychological Disorders among Health Care Staffs in Central Hospitals of Hanoi, Vietnam, 2020. (March 2021) - Lan, Vu Thi Hoang; Dzung, Le Thanh; Quyen, Bui Thi Tu; Nha, Pham Ba; Linh, Nguyen Thuy; Hoang, Le Tu; Nghia, Nguyen Quang; Hung, Duong Duc
This study aims to examine the impact of undergoing a central quarantine due to the lockdown of Bach Mai hospital on the psychological disorders and identify associated factors with depression among hospital employees in central hospitals of Hanoi, Vietnam. Employing a cross-sectional design, the study collected data from staff working in the lockdown hospital and other central hospitals during 1 week after the lockdown happened. The sample size included 373 staff from 3 hospitals, the study time was. Depression was tested using PH-Q9 scale. Multivariate logistics regression was employed to test for the impact of central quarantine on depression and identify other significant related factors. The study confirmed a high burden of psychological issues that hospital employees were facing. Staff working in the lockdown hospital had 2.3 times higher odds of being perceived depression than others. Those who contact directly about 21 to 20 patients/day had 3.19-times higher odds of being perceived depression than others. Staff who being stigmatization associated with COVID-19 had 2.63 times higher odds of perceived depression than others. Reducing these associated factors to depression may help to reduce the psychological burden HEs have to cope with during the pandemic.